Evaluation of Eggplant Accessions for Resistance to Bacterial Wilt Caused by Ralstonia solanacearum (E.F. Smith) Yabuuchi et Al. - C Gopalakrishnan; T H Singh; Rashmi B Artal (Journal of Horticultural Sciences, 2014)
Forty-one eggplant accessions were screened in a sick plot for bacterial wilt resistance at Indian Institute of Horticultural Research, Hessaraghatta, Bengaluru. Nine accessions, viz., IIHR-322, AVT-IIRES-1, AVT-IIRES-2, AVT-IIRES-4, AVT-IIRES-5, IIHR500-A, BPLH-1, IIHR-3 and IIHR-5 showed highly resistant reaction, with no wilting of plants; five accessions, viz., RES-2, RES-5, RES-6, 37-36-4-4 and 36-37-13, showed resistance reaction per cent wilt 3.33 -10.0. Two accessions, viz., 36-37-3 and 37-4-20, showed moderately resistant reaction, with 11.0 and 12.0 per cent wilt incidence, respectively; while, 22 accessions were 'moderately susceptible to highly susceptible', with wilt incidence ranging from 25.45 to 100.0%.